Integrating digital literacy into South African academic literacy: An autoethnographic exploration of evolving interventions - Nel, Mariska (Journal for Language Teaching, 2025)
The rapid advancement of technology has transformed the educational landscape, prompting institutions worldwide to integrate technology into their curricula to enhance personalized learning and student engagement. However, this advancement has also exacerbated existing educational inequities, particularly in developing countries like South Africa. Academic literacy is an established intervention aimed to support first-time entering students in higher education with their academic acculturation (Alexander et al., 2005; Council on Higher Education, 2017; Nel & Janse van Rensburg, 2022). However, while current academic literacy interventions provide crucial support, these interventions lack the necessary components to fully equip students for success in this technologically driven era. Using an explorative auto-ethnographic research design the inter-section of technological advancements and the pressing need for improved academic literacy interventions is investigated. Finally, the argument is made that the increasing digital divide necessitates a modernized approach to the development of literacy skills – one that seamlessly inte-grates digital literacy into existing academic literacy frameworks – to enhance student success and empower them to thrive in the digital age.